2009
DOI: 10.1017/s0022029909004154
|View full text |Cite
|
Sign up to set email alerts
|

Administration of a live culture ofLactococcus lactisDPC 3147 into the bovine mammary gland stimulates the local host immune response, particularlyIL-1β andIL-8gene expression

Abstract: Mastitis is one of the most costly diseases to the dairy farming industry. Conventional antibiotic therapy is often unsatisfactory for successful treatment of mastitis and alternative treatments are continually under investigation. We have previously demonstrated, in two separate field trials, that a probiotic culture, Lactococcus lactis DPC 3147, was comparable to antibiotic therapy to treat bovine mastitis. To understand the mode of action of this therapeutic, we looked at the detailed immune response of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 35 publications
4
46
1
Order By: Relevance
“…Similar results to those found in this study were reported by BEECHER et al (2009), who evaluated in detail the immune response following the infusion of live cultures of Lactococcus lactis DPC 3147 into the mammary glands of cows. These authors noted that during the first 72 hours PI, quarters where L. lactis was applied showed higher levels of SCC than control quarters.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Similar results to those found in this study were reported by BEECHER et al (2009), who evaluated in detail the immune response following the infusion of live cultures of Lactococcus lactis DPC 3147 into the mammary glands of cows. These authors noted that during the first 72 hours PI, quarters where L. lactis was applied showed higher levels of SCC than control quarters.…”
Section: Resultssupporting
confidence: 80%
“…For this reason, new mastitis control methods continue to be studied. The use of live lactic acid bacterial cultures as therapeutic agents against bovine mastitis is currently a topic of research (BEECHER et al, 2009;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactobacillus has been used widely as a feed additive in the dairy cattle industry to improve intestinal health, feed conversion efficiency and milk production (Chen et al 2013). Dietary supplementation of Lactobacillus was reported to increase milk production, reduce the count of somatic cells in milk (Jiang et al 2008) and reduce the probability of mastitis by positively regulating interleukin-1 (IL-1) and IL-8 in the mammary gland (Beecher et al 2009). However, those studies did not document the specific strain of L. acidophilus, and to our knowledge, there is no research evaluating the supplemental efficacy of L. acidophilus in in vitro fermentation experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Such properties are harnessed in the development of vaginal probiotics used to prevent urogenital infections (18). Recently, the use of a bacteriocin-producing Lactococcus lactis strain was reported to be as efficient as a conventional antibiotic therapy to treat staphylococcal mastitis (19,20). Encouraging results were also obtained with a Lactobacillus perolens strain which was able to inhibit several mastitis-causing pathogens in vitro, to coaggregate with all of them, and to adhere to bovine teat canal epithelial cells without affecting udder aspect or the appearance of milk (21).…”
mentioning
confidence: 99%